2020
DOI: 10.1016/j.scitotenv.2020.138143
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and physiological responses of two clam species to Triclosan combined with climate change scenario

Abstract: Ocean acidification and warming are among the man-induced factors that most likely impact aquatic wildlife worldwide. Besides effects caused by temperature rise and lowered pH conditions, chemicals of current use can also adversely affect aquatic organisms. Both climate change and emerging pollutants, including toxic impacts in marine invertebrates, have been investigated in recent years. However, less information is available on the combined effects of these physical and chemical stressors that, in nature, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…Many researchers pointed that consumers’ attitudes motivate consumption behavioral intention ( Costell et al, 2010 ). Other previous literature investigated consumers’ perception and satisfaction as a significant component of consumers’ attitudes and loyalty ( Costa et al, 2020 ; Rahman et al, 2021 ). Sadiq et al (2021) reported that consumers’ attitude is a crucial dimension in determining consumption behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers pointed that consumers’ attitudes motivate consumption behavioral intention ( Costell et al, 2010 ). Other previous literature investigated consumers’ perception and satisfaction as a significant component of consumers’ attitudes and loyalty ( Costa et al, 2020 ; Rahman et al, 2021 ). Sadiq et al (2021) reported that consumers’ attitude is a crucial dimension in determining consumption behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TCS exposure (100 µM) in vitro affected mussel CEs causing a 72% inhibition of the activity, corroborating previous results (Solé and Sanchez-Hernandez, 2018), while its effects on crustaceans was more moderate albeit significant (≈ 20%). TCS is able to accumulate in bivalves and cause in vivo metabolic disturbances (Costa et al, 2020;Kookana et al, 2013;Matozzo et al, 2012;Pirone et al, 2019;Serra-Compte et al, 2018) but no inclusion of CE measures had been considered in these former studies. TCS toxicity was assessed in the marine decapod crustacean Palaemon varians using an avoidance test (Araujo et al, 2019) and in the marine gastropod Haliotis tuberculate through in vitro toxicity tests using gill cell cultures and hemocytes (Gaume et al, 2013).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It is well known that heat stress caused by elevated temperature constitutes a principal challenge to marine organisms, affecting their metabolism (Louis et al, 2020; which can make them more sensitive to chemical exposure. Conversely, chemical exposure may affect the organism ability to cope with thermal stress (Nardi et al, 2018 ;Costa et al, 2020). Our results revealed that the combined effect of levonorgestrel and higher temperature of 28°C caused a high lipoperoxidation marked by elevated TBARS production.…”
Section: Biochemical Responsesmentioning
confidence: 50%
“…Numerous studies have reported the potential negative impact of increased temperature on bivalves, such as changes in their respiratory rate (Jansen et al 2009), their metabolism (Anestis et al 2007) and their immune responses (Malagoli et al, 2007), altering sexual maturation (Martıńez and Pérez, 2003), reducing survival (Arnberg et al, 2013), inducing abnormal larval development and reducing fertility and growth of larvae and juveniles (Nguyen et al, 2012). This toxic situation can be more dramatic when the marine organism is exposed to thermal and chemical stresses; because chemical pollutants can be strongly affected by warming seawater and the sensitivity of organisms to chemicals can be modi ed by heat stress (Costa et al, 2020. In addition, pollutants can damage the ability of organisms to respond to rapid increases in temperature (Hooper et al, 2013;Noyes and Lema, 2015).…”
Section: Introductionmentioning
confidence: 99%